QUANTUM SCATTERING VIA THE LOG DERIVATIVE VERSION OF THE KOHN VARIATIONAL PRINCIPLE - Manolopoulos, D; Wyatt, R (1988)
The log derivative version of Kohn's variational principle is used as a setting for a new numerical approach to quantum scattering problems. In particular, a new radial basis set is devised which is both (a) ideally suited to the log derivative boundary value problem, and (b) directly amenable to a discrete representation based on Gauss-Lobatto quadrature. This discrete representation greatly facilitates the evaluation of the exchange integrals which arise in Miller's formulation of chemical reactive scattering, and therefore significantly simplifies calculations which exploit this formulation. Applications to the 3-D H+H2 reaction clearly demonstrate the practical utility of the method. © 1988.